Pemanfaatan Multimedia pada Edukasi untuk Meningkatkan Kepatuhan dan Kualitas Hidup Pasien Transplantasi Ginjal - Pratiwi, Nita Indah; Yulia, Yulia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of the use of multimedia in education in improving compliance and quality of life of kidney transplant patients. The method used in writing this article is literature review on three databases ProQuest, PubMed, ScienceDirect using the keywords multimedia, education, adherence AND 'quality of life' and 'kidney transplantation’. The results of a review show that the types of multimedia that can be used in education include animated videos, applications and artificial intelligence chatbots. The conclusion of this study is that the use of multimedia in education effectively improves adherence and quality of life for kidney transplant patients. However, the use of multimedia in education must consider accessibility, the elderly population and patients with visual and/or cognitive impairments. Keywords : Education, Adherence, Quality of life, Multimedia, Kidney transplantation